Alto Santana : relação entre a toponímia do setor e os lugares quilombolas - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This study aims to describe and analyze the toponymy of the Alto Santana Sector (SAS), located in the city of Goiás, highlighting the relationship between the toponyms (names of streets, lanes, squares and other public spaces) and the urban places in the sector, which is also a quilombola territory. It is based on the premise that the naming of urban spaces does not occur randomly, but reflects historical processes marked by resistance, exclusion and symbolic power, elements that are manifested in cultural practices and the construction of collective identity. The aim is therefore to describe and analyze the toponyms of the SAS, in order to identify linguistic traits that may reveal meanings related to experiences of social, economic and cultural violence in their respective designations. The study thus questions whether the region's toponyms reflect the identity of the quilombola community that lives there or whether their names follow externally imposed standards. The research adopts a qualitative and interpretative approach, based on the onomasiological method, a documentary survey and a literature review. The corpus analyzed comprises 23 toponyms recorded in official city documents, examined from the perspective of toponymic studies by Dick (1990), Biderman (1998), Isquerdo (1997) and other researchers in the field. To this end, the information was compared using taxonomic categories that classify names according to their physical and anthropocultural nature. The results indicate that most of the toponymy in the SAS is made up of hierotoponyms (hagiotoponyms and anthropotoponyms) linked to the Catholic tradition. On the other hand, the toponyms associated with the culture and identity of the black community are in the minority, which suggests an imposed naming process, and not necessarily a spontaneous or representative one. Thus, the analysis of the toponymy of the SAS contributes to the debate on policies of memory, identity and representation in contexts marked by colonial heritage, highlighting the tensions that exist in the attribution of names to urban spaces.
Alto Santana : relationship between the toponymy of the sector and quilombola sites
Keywords: Topônimo; Interculturalidade; Quilombo; Toponym; Interculturality; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LETRAS::LINGUA PORTUGUESA